Mycobacterial protein PE_PGRS30 induces macrophage apoptosis through prohibitin 2 mitochondrial function interference - Matsumura, Kazunori; Takaki, Satoshi; Kirikae, Teruo (Frontiers in Microbiology, 2023)
PE_PGRS30 belongs to the PE_PGRS protein family and is characterized by a conserved Pro-Glu (PE) domain and a typically polymorphic GC-rich sequence (PGRS) domain. PE_PGRS30 is a virulence factor of Mycobacterium tuberculosis that induces macrophage cell death. We found that RAW264.7 cells and murine alveolar macrophages underwent apoptosis in response to PE_PGRS30. The host protein prohibitin 2 (PHB2) was identified as a target molecule. PE_PGRS30 and PHB2 interact via the PGRS domain and mitochondrial targeting sequence, respectively. PHB2 overexpression reduced macrophage apoptosis in response to PE_PGRS30. PE_PGRS30 co-localized with PHB2, not in mitochondria, but in lysosomes. The maintenance of mitochondrial structure by PHB2 was impaired in response to the PGRS domain. These results indicated that PE_PGRS30 reduces PHB2 in mitochondria, resulting in mitochondrial dysfunction and cellular apoptosis.